Exploring the burdens of women living with Fabry disease in Japan: A patient survey of 62 respondents - Masahisa Kobayashi; Ikuko Kaku; Nanae Goto; Mio Tsuchiya; Norio Sakai (Molecular Genetics and Metabolism Reports)
The challenges encountered by women living with Fabry disease in Japan are not well understood. This study aimed to elucidate the experiences of women with Fabry disease and their support networks from both female and male perspectives. A 22-question survey was conducted among patients with Fabry disease and their caregivers (≥18 years) in Japan between August and October 2023. Sixty-two recipients completed the questionnaire (11.5 % response rate); 47 (75.8 %) were female and the mean age was 52.4 years. Overall, 51 respondents (82.3 %) identified as patients, 2 (3.2 %) as caregivers, 6 (9.7 %) as both a patient and caregiver, and 3 (4.8 %) as “other”. In total, 43 respondents (69.4 %) were women with Fabry disease. Among life events surveyed, Fabry disease had the greatest impact for women during family planning. The most commonly reported concerns for women were inheritance of Fabry disease and impact on children, the main reasons for which were prejudice, stigma, and sense of guilt associated with inheritance. In all, 28.1 % of respondents felt family and colleagues understood women's challenges with Fabry disease, while 37.9 % believed their primary care physicians and 48.3 % felt their specialist physicians understood these challenges; 26.3 % thought women received tailored care, and 75.9 % felt the condition affects mental health. Women with Fabry disease in Japan face substantial emotional burdens and lack support from their community and physicians. Healthcare professionals can play a pivotal role by offering genetic counseling and developing support programs to alleviate mental burdens and provide education about the disease and family planning implications.